Formulation and Development of Mucoadhesive Tablet of Diltiazem Hydrochloride - DHARA B. PATEL,; MADHABHAI M. PATEL, (International Journal of Pharma and Bio Sciences, 2010)
Mucoadhesive tablets of diltiazem hydrochloride were formulated as matrix tablets employing, polyethylene oxide (Polyox) and hydroxypropylmethylcellulose (HPMC) and were investigated for mucoadhesion and drug release behavior. Tablets formulated using different viscosity grades of Polyox showed the drug release decreased with viscosity of Polyox increased. Tablet prepared with Polyox alone were slowly eroded and were dissolved completely within 6-10 hours. The mucoadhesive strength of the matrices increased with increase in polymer content. When HPMC was incorporated, the tablets remained intact and provided slow release of diltiazem for over 12 hr. A 32 full factorial design was conducted to optimized the formulation. The kinetic modeling study of all batches was shown anomalous pattern of drug release. The drug was released by both erosion and diffusion mechanism. Thus the developed formulation can be suitable for targeted delivery of diltiazem in upper part of GI tract where the absorption of diltiazem is more confined.